2019
DOI: 10.5586/aa.1758
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed extracts’ multifactorial action: influence on physiological and biochemical status of Solanaceae plants

Abstract: Seaweeds are one of the important marine bioresources which are nowadays termed as eco-friendly stimulators of crop growth, stress tolerance, and yielding. In this review, we give an update of the current state of our understanding of the seaweed extracts (SWE) effects on the physiological alterations they induce in Solanaceae vegetables. SWE may provide a powerful and environmentally friendly approach to nutrient management. A pool of common bioactive molecules of SWE provides enhancement of the antioxidant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
1
9
0
10
Order By: Relevance
“…In general, seaweed extracts enhance plant growth and quality and improve the resistance to climatic changes because they are rich in fatty acids, minerals and polysaccharides [54]. The chemical and biochemical constituents of any seaweed extract act as biostimulants that work synergistically [55,56]. There was a good agreement with the results of previous studies that indicated the beneficial effects of diluted seaweed extracts on plants such as artichoke [15,42].…”
Section: Head Qualitysupporting
confidence: 81%
“…In general, seaweed extracts enhance plant growth and quality and improve the resistance to climatic changes because they are rich in fatty acids, minerals and polysaccharides [54]. The chemical and biochemical constituents of any seaweed extract act as biostimulants that work synergistically [55,56]. There was a good agreement with the results of previous studies that indicated the beneficial effects of diluted seaweed extracts on plants such as artichoke [15,42].…”
Section: Head Qualitysupporting
confidence: 81%
“…Furthermore, the application of SWE has also been associated with an increase in plant tolerance to biotic and abiotic stresses [100][101][102]. In recent years, there has been a growing interest in SWE amongst the scientific community and the agricultural industry, as several studies indicate a positive influence of SWE in crop production in both normal and stress conditions [103][104][105]. However, it has been shown that the efficacy of seaweed extracts may depend on whether or not a stress is present or absent, the type of stress involved, the type of extract and it biochemical characteristics [101].…”
Section: Seaweed Extractsmentioning
confidence: 99%
“…Garlic juice used in vitro limits the growth of bacteria (genus Agrobacterium, Erwinia, Pseudomonas, Xanthomonas) and fungi (Alternaria alternata, Fusarium moniliforme, Cercospora arachidicola, Colletotrichum coccodes, Botrytis cinerea, Rhizoctonia solani) [6,26,27]. Many authors have reported high efficiency of allicin under field conditions [28][29][30]. Spraying sweet pepper plants several times with a solution of garlic pulp extract (Bioczos Liquid preparation) improved plants' health and was more effective than azoxystrobin treatment (Amistar 250 SC fungicide) [26].…”
Section: Natural Compounds Against Plant Diseasesmentioning
confidence: 99%